Chemodivergent Palladium‐Catalyzed Processes: Role of Versatile Ligands. Issue 23 (28th October 2015) - Nava, Paola; Clavier, Hervé; Gimbert, Yves; Giordano, Laurent; Buono, Gérard; Humbel, Stéphane
Abstract: Whereas the reaction of norbornadiene with terminal alkynes in the presence of a phosphapalladacycle catalyst leads to the formation of hydroalkynation products, the use of phosphinous acid–phosphinito‐containing palladium complexes gives rise to formal [2+1] cycloadducts. An experimental and computational approach was employed to study the mechanisms of the palladium‐promoted hydroalkynation and [2+1] cycloaddition. On the one hand, experiments highlight the crucial role of acidolysis steps on the catalytic activities. On the other hand, DFT calculations demonstrate the specificity of the phosphinito–phosphinous acid ligands, that is, the non‐equivalence of the two phosphorus atoms but the interchangeability of their properties. These results may have important implications for the mechanism of other palladium‐catalyzed transformations especially those involving phosphapalladacycles and phosphinous acid–phosphinito‐containing palladium complexes. Abstract : Pd ligands tip the scales : An experimental and computational approach is employed to study the mechanisms of the palladium‐promoted hydroalkynation and [2+1] cycloaddition between norbornadiene and terminal alkynes. This study highlights the specificity of the phosphinito–phosphinous acid ligands.